Pengembangan E-LKPD Berbasis Google Sites Bercirikan Pendekatan Saintifik untuk Membangun Pemahaman Konsep Matriks - Wisnu Dharma Basudewa; Diesty Hayuhantika (Institut Agama Islam Negeri Curup, 2022)
One way to build understanding of the concept is to make innovations about E-LKPD. This study is aims to develop on process, the process result an E-LKPD based google sites on matrix material using a scientific approach to build a valid understanding of students' concepts. This study refers to one development model, namely the Four-D (4-D) is Define, Design, Development, and Disseminate. In this study, the researcher modified the Four-D with 3 stages, namely Define, Design, and Development. The results showed that the feasibility level of the E-LKPD based google sites on the matrix material based on the research of media experts all aspects got a total score of 101, so that when presented the validity of the media it got a value of 78.9% with the